2017
DOI: 10.29333/iejme/610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrating children’s literature and SQRQCQ problem solving learning on elementary school student’s mathematical reading comprehension skill

Abstract: The aim of this research was to examine the effect of learning application of SQRQCQ problem solving with children's literature toward the reading comprehension skills of elementary school students. This research involved 105 fifth grade students in three intact classes in Bandung. The quasi-experimental research with control class without pre-test was done, but previously prior math knowledge test was conducted to find out the equality of each class ability and grouping them into high, medium, and low. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Manakala menurut Gurat (2018), matlamat asas mengajar murid berkaitan kebolehan ini adalah untuk membantu mereka menjadi lebih mahir dalam menyelesaikan pelbagai masalah matematik yang timbul dalam kehidupan seharian. Pengkaji kini dengan itu lebih menumpukan perhatian untuk membantu pelajar menguasai kebolehan yang akan memupuk kreativiti mereka (Suastika 2017) serta kefahaman mereka terhadap matematik (Mulyati et al, 2017) memandangkan kebolehan ini dapat memupuk dan membina daya imaginasi pelajar (Wibowo et al, 2017).…”
Section: Kemahiran Penyelesaian Masalah Matematikunclassified
“…Manakala menurut Gurat (2018), matlamat asas mengajar murid berkaitan kebolehan ini adalah untuk membantu mereka menjadi lebih mahir dalam menyelesaikan pelbagai masalah matematik yang timbul dalam kehidupan seharian. Pengkaji kini dengan itu lebih menumpukan perhatian untuk membantu pelajar menguasai kebolehan yang akan memupuk kreativiti mereka (Suastika 2017) serta kefahaman mereka terhadap matematik (Mulyati et al, 2017) memandangkan kebolehan ini dapat memupuk dan membina daya imaginasi pelajar (Wibowo et al, 2017).…”
Section: Kemahiran Penyelesaian Masalah Matematikunclassified
“…For example, Abdelaal and Sase (2014) found a positive relationship between HPK and reading comprehension, while no significant relationship was found between LPK and reading comprehension. In addition, Mulyati et al (2017) found that students with HPK performed better than those with LPK in mathematical reading comprehension skills. In addition, past research also showed that prior knowledge was associated with learners' reading motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pemecahan masalah merupakan bagian penting dari pembelajaran matematika sehingga pemecahan masalah harus terdapat dalam kurikulum matematika sekolah. Pemecahan masalah merupakan jantung dalam belajar matematika karena semua kegiatan matematika membutuhkan tindakan pemecahan masalah (Pimta, Tayruakham, and Nuangchale, 2009;Yeliz, 2015), dapat meningkatkan daya imajinasi siswa (Wibowo et al, 2017), mengembangkan kreativitas siswa (Suastika, 2017) dan menunjang kemampuan pemahaman siswa (Mulyati, Herman, and Mulyana, 2017). Laine et al (2012) menyatakan bahwa pemecahan masalah modern telah dibuat pada tahun 1950an oleh George Polya, ketika dia memperkenalkan empat langkah untuk memecahkan masalah: memahami masalah, merencanakan penyelesaiannya, melaksanakan rencana penyelesaian masalah, dan melakukan pemeriksaan kembali terhadap penyelesaiannya.…”
Section: Pendahuluanunclassified